An Examination of Students' Moral Character Experiences Using the Four Component Model and Self-Evolution Theory. Issue 2 (3rd April 2022) - King, Patricia M.; Sparks, Tim
Abstract: In this article, we introduce the four component model (FCM), which describes both the internal processes that play distinct roles in the production of moral behavior and their associated sets of relevant, teachable skills. We use this model as an analytic framework to examine college students' moral character experiences reported in the Wabash National Study. We also examine whether the skills they used were related to their progress toward self-authorship. We report which FCM skills were used most frequently and that participants who were more self-authored used different sets of skills than their counterparts who held less complex meaning-making assumptions. We conclude by discussing the complexity of moral character and the implications of using the FCM for practitioners and researchers working in this domain.